Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/b978-0-444-62721-6.00002-0
|View full text |Cite
|
Sign up to set email alerts
|

The Advertising-Financed Business Model in Two-Sided Media Markets

Abstract: This chapter focuses on the economic mechanisms at work in recent models of advertising …nance in media markets developed around the concept of two-sided markets. The objective is to highlight new and original insights from this approach, and to clarify the conceptual aspects. The chapter …rst develops a canonical model of two-sided markets for advertising, where platforms deliver content to consumers and resell their "attention" to advertisers. A key distinction is drawn between free media and pay media, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 101 publications
1
29
0
Order By: Relevance
“…For surveys of the literature, see Anderson, Strömberg, and Waldfogel (), in particular chapters by Anderson and Jullien (), Foros, Kind, and Sørgard (), and Peitz and Reisinger ().…”
mentioning
confidence: 99%
“…For surveys of the literature, see Anderson, Strömberg, and Waldfogel (), in particular chapters by Anderson and Jullien (), Foros, Kind, and Sørgard (), and Peitz and Reisinger ().…”
mentioning
confidence: 99%
“…where F is the subscription fee, and Φ > 0 denotes a user's average disutility (e.g., inconvenience) of watching one ad. We assume that the total disutility of watching ads linearly increases with the number of watched ads [20], [32]. In Sections III-A and IV-A, we will analyze the users' optimal decisions r * (θ, ω) and x * (θ, ω).…”
Section: B Usersmentioning
confidence: 99%
“…In this study, the profit from selling online content was compared with the profit from renting for a few periods. One study that focused on the impact of the promotional value of a free service was also conducted [19]. Another study revealed that a free music streaming service stimulated overall consumption, thereby increasing profits from advertisements [20].…”
Section: Related Literaturementioning
confidence: 99%